PENYELESAIAN SENGKETA TAPAL BATAS ANTARA KABUPATEN LEBONG DENGAN KABUPATEN BENGKULU UTARA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN (JURNAL HUKUM SEHASEN, 2017)
On the issue of the boundary disputes between Lebong District and North Bengkulu Regency, which is caused by the Law of Establishment of their respective regions and the extension of Lebong Regency region which resulted in the development of territory by Lebong Regency against some areas of North Bengkulu Regency. The objectives of the research are (1) to know the cause of conflict / disputes between Lebong District and North Bengkulu Regency, (2) to explain the alternative of settlement of border disputes between Lebong Regency and North Bengkulu Regency according to the laws and regulations. The type of research used in this study is normative, because the material discussed prioritizes review in terms of legislation related to the Settlement of Boundary Disputes between Lebong District and North Bengkulu Regency Based on Law Number 32 Year 2004 regarding Regional Government. The result of the research shows that 1) Alternative of settlement of boundary disputes between Lebong Regency and North Bengkulu Regency according to the laws and regulations, namely legal settlement and non-legal settlement.Keywords: dispute, prohibition, alternative